Oral glutamine challenge is a marker of altered ammonia metabolism and predicts the risk of hepatic encephalopathy. (1st December 2019) - Ampuero, Javier; Gil, Antonio; Viloria, María del Mar; Rico, María Carmen; Millán, Raquel; Camacho, Inés; Romero‐Gómez, Manuel
Abstract: Background: The current therapies for hepatic encephalopathy (HE) are not completely effective in all patients, probably due to the physiopathological heterogeneity and the different conditions underlying the bout of HE. We hypothesized that oral glutamine challenge (OGC) is able to predict the risk of HE through the identification of various features and types of HE. Methods: We included 238 cirrhotic patients (198 without and 40 with a previous HE episode) that underwent OGC, obtaining baseline and 60 minutes post‐load ammonia levels. Combined evaluation of baseline hyperammonemia (>78 mcg/dL) and impaired OGC (Δ >32 mcg/dL) defined low‐, intermediate‐ and high‐risk groups. Patients were censored at HE, liver transplantation and death or 6 years of follow‐up. Results: The 28.3% (56/198) of the main cohort suffered from HE during the follow‐up. In the competing risk analysis, both intermediate‐ (subhazard ratio (sHR) 2.01 (95% CI 1.00‐4.14); P  = .048) and high‐risk groups (sHR 4.67 (95% CI 2.19‐9.98); P  = .0001) were associated with the first HE episode, together with age and albumin. Similar results were found for repeated HE events. The cumulative incidence for HE of the high‐risk group was two and four times greater than the intermediate‐ and low‐risk groups, respectively. The HE grade was also higher in individuals with the greatest risk ( P  = .035). The most common precipitant factor was diuretics in the high‐risk group, while infections and electrolyte imbalance predominated in the rest of patients. Conclusion: Oral glutamine challenge identified patients at risk of HE and defined specific features of the episodes. This tool could be useful in the decision‐making process for the adequate management of HE.